Water policy, politics, and practice: The case of Kitui County, Kenya - Koehler, Johanna; Nyaga, Cliff; Hope, Rob; Kiamba, Pauline; Gladstone, Nancy; Thomas, Mike; Mumma, Albert; Trevett, Andrew (Frontiers in Water, 2022)
The devolution of governance to county level in Kenya provides a window for innovation in water policy and practice, critical to improving water security in rural areas where almost half of households lack basic water services. In rural Kitui County, Kenya, a number of projects supported by different funders have served as policy experiments over the past ten years. We apply an action-oriented knowledge framework to explore the kinds of knowledge that have been produced in the course of these interventions and reflect on what kinds of knowledge are contributing to institutional change and how they are contributing to sustainability in the rural water sector. Actionable recommendations for the further development of county-level water policy include: First, ensure local ownership of the policy-making process whilst enabling appropriate technical and legal support; second, take long timeframes of institutional change into account in donor programming; third, establish water, sanitation and hygiene forums bringing diverse actors within the sector together to build cohesion, facilitate knowledge exchange, enable collaborative learning, and deliver collective action.